Globalization and Corporate Social Responsibility in the 21st Century - Fiestas Pflucker, Jorge Adalberto (2019)
In the business area there are major changes due to globalization, nowadays markets must be more competitive and dynamic in the face of social demands that demand the return to society of the benefits that organizations earn. Corporate Social Responsibility (CSR) has gained strength in recent decades with globalization, the acceleration of the economy, technologies and the care of the environment; CSR is the ethics of business economic activity that includes a set of social, economic, and environmental commitments that organizations have with the environment, where sustainability is the main criterion of performance with greater transparency without leaving aside the interests of the company. We live in a world that changes rapidly and in a complex way that it is difficult to distinguish which are the most significant changes and those that will have the greatest predominance in the society of tomorrow.